How Malleable is the ‘Gold Standard’?: A Case Study in Respect of South Africa’s Access to Information Regime - Peekhaus, Wilhelm (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper examines the difficulties encountered by Biowatch, a South African civil society environmental organisation, in its attempts to obtain access to government information in respect of genetically engineered plants. The elaboration of the case is based on interviews conducted with the Director of Biowatch and the organisation’s legal counsel. Cette communication porte sur les difficultés rencontrées par Biowatch, une organisation environnementale de la société civile sud-africaine, lors de ses tentatives d’obtenir accès aux données gouvernementales relativement aux plantes issues du génie génétique. L’élaboration du cas se base sur des entrevues menées auprès du directeur de Biowatch et le conseiller juridique de l’organisation.